Effectiveness of Microcurrent Stimulation in Preserving Retinal Function of Blind Leading Retinal Degeneration and Optic Neuropathy: A Systematic Review. Issue 6 (13th May 2021) - Liu, Jinfeng; Tong, Kelvin; Lin, Youhong; Lee, Vincent W. H.; So, Kwok Fai; Shih, Kendrick Co; Lai, Jimmy S. M.; Chiu, Kin
Abstract: Objectives: To systematically identify and summarize the effectiveness and the parameters of electrical stimulation (ES) for the preservation of visual function in major retinal degeneration and optic neuropathy. Materials and Methods: A systematic review of clinical studies, using ES therapy in patients with blind leading retinal degenerations, including retinitis pigmentosa (RP), age‐related macular degeneration (AMD), glaucoma, retinal vein occlusion (RVO), retinal artery occlusion (RAO), and optic neuropathy was conducted. PubMed, EMBASE, Cochrane Library, and Web of Science were searched for relevant interventional studies including randomized controlled trials (RCTs) and observational studies. Results: A total of 10 RCTs and 15 observational studies were included. Transcorneal ES (TcES), transpalpebral ES (TpES), transdermal ES (TdES), and repetitive transorbital alternating current stimulation (rtACS) were used for the treatment of the patients. ES using 20 Hz biphasic pulses with current strength at 150%–200% of individual electrical phosphene threshold (EPT) for RP patients showed improved retinal function detected by visual acuity (VA), visual field (VF), or electrical retinal graphs (ERG). rtACS on patients with optic neuropathy showed significant preservation of VA and VF. Clinical studies on AMD, RAO, and glaucoma indicated promising protective effects of ES on the visual function, though the amount of evidence is limited. Conclusions: ES treatment has promising therapeutic effects on RP and optic neuropathy. More large‐scale RCT studies should be conducted to elucidate the potential of ES, especially on AMD, RAO, and glaucoma. A comparison of the effects by different ES methods in the same disease populations is still lacking. Parameters of the electric current and sensitive detection method should be optimized for the evaluation of ES treatment effects in future studies.